Impact of Soil and Water Conservation Measures on Hydrology of Micro) Watersheds in Madhya Pradesh - Reddy, K.S.; Gharde, K.D.; Bhandarkar, D.M.; Kumar, Nirmal (Journal of Soil and Water Conservation, 2022)
Soil and water conservation measures are meant to reduce soil erosion and utilize rainwater. The measures include construction of contour bunds, contour trenches, graded terraces, check dams, dugout ponds, open wells, and similar other works. Some of the works done by the agencies of the Madhya Pradesh Govt. are analyzed and discussed in the paper. The data analyzed pertain to the catchments of the Narmada river and the analysis indicates that there has been increase in the base flow from 181 to 336 cumecs before and after the implementation of watershed programs by Rajiv Gandhi Mission for Watershed Management in Madhya Pradesh The paper also deals with some suggestions for effective implementation of the on-going watershed programs.